Brexit and the implications for financial services - Patricia Jackson (SUERF - The European Money and Finance Forum, 2017)
On 23rd February 2017, SUERF and EY organized a conference on "Brexit and the Implications for Financial Services" at EY's offices, Churchill Place, Canary Wharf, London. While the outcome of the Brexit negotiations remains highly uncertain, the conference discussed the burning questions for financial firms, markets and regulators with a range of different viewpoints expressed on a number of important themes: the systemic risks from Brexit; the possible role of equivalence versus passporting to continue to facilitate cross-European financial transactions; the effects on the deep wholesale markets located in London and the question as to whether the sheer size and interconnectedness of London as a financial center implied that it would still act as a magnet for European business; the effects on Europe if the result created fragmentation of markets and CCPs; and the implications for bank, insurer and asset manager business models, in particular whether Brexit would act as a catalyst for restructuring and retrenchment from activity in the EU27.
Keywords: F13; F15; F23; F30; F33; F36; F42; F52; F53; F55; F62; F65; G01; G15; G18; G21; G22; G23; G24; G28; K23; 330; Brexit; Banking; Insurance; Asset Management; Clearing; Third Country Equivalence; Globalisation and anti-globalisation; Monetary policy; Integration of markets; Financial stability; Financial centres; Central counterparties; market infrastructures; financial regulation; Financial markets; business models; European Union; Single market; International trade; Political negotiations; International cooperation